2007
DOI: 10.1111/j.1572-0241.2006.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Sulfate and Hydrogen Metabolism in the Human Colon by Changing Intestinal Transit Rate

Abstract: Both sulfate supplements and changes in intestinal transit rate markedly alter the activity of the colonic bacterial flora with respect to sulfate metabolism and hydrogen disposal. Dietary influences on intestinal transit and sulfate consumption may influence disease processes. While a variety of processes govern sulfate metabolism and hydrogen disposal, our knowledge is far from complete. How far the observed changes in sulfate metabolism seen in certain diseases are relevant to the pathogenesis of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…56,63,65,67,79,82 However, the link to symptoms and other pathogenetic and pathophysiological factors is unclear in the majority of these studies (although some of the latest studies have demonstrated associations) ( Table 1). Moreover, whether these alterations are linked to disease per se, or are merely consequences of other factors with known effects on gut microbiota composition, such as diet, [83][84][85][86] use of drugs or changes in gastrointestinal transit (reflecting abnormalities in gastrointestinal motility), [85][86][87][88] is still poorly defined and needs to be addressed in future studies.…”
Section: Gut Microbiota In Ibsmentioning
confidence: 98%
“…56,63,65,67,79,82 However, the link to symptoms and other pathogenetic and pathophysiological factors is unclear in the majority of these studies (although some of the latest studies have demonstrated associations) ( Table 1). Moreover, whether these alterations are linked to disease per se, or are merely consequences of other factors with known effects on gut microbiota composition, such as diet, [83][84][85][86] use of drugs or changes in gastrointestinal transit (reflecting abnormalities in gastrointestinal motility), [85][86][87][88] is still poorly defined and needs to be addressed in future studies.…”
Section: Gut Microbiota In Ibsmentioning
confidence: 98%
“…Red meat contains high amounts of sulfur amino acids, whereas processed foods and alcoholic beverages contain large amounts of sulfite or sulfate [23]. It was suggested that a high sulfur diet results in the generation of H 2 S and mucosal damage in the colon.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Fermentation of dietary and mucinous sulfate and sulfur amino acids, such as methionine, cystine, cysteine and taurine, by sulfate-reducing bacteria results in the production of hydrogen sulfide (H 2 S) [23,24]. H 2 S is an extremely toxic agent (LD 50 for rodents comparable to cyanide [25]) and luminal H 2 S concentrations in the large intestine range between 1.0 and 2.4 mM [26].…”
Section: Products Of Protein Fermentationmentioning
confidence: 99%
“…Recent evidences showed that gut microbiota plays a very important role & however, types and its frequencies of microbial organisms constituting gut microbiota in each individual are very different from each other at the species levels. The composition of the jut microbiota is established during the fi rst few years of life and is likely shaped by multiple factors, including maternal vertical transmission, genetic makeup, diet, antibiotics, infections, and stress (Hopkins and Sharp, 2001; Lewis and Cochrane, 2007;Cecilia and Sonja, 2010;Brian et al, 2013). Since the jut microbiota is a key player of the mucosal homeostasis, dysregulation of the intestinal mucosa homeostasis is consequentially implicated in the progression of disorders.…”
Section: Introductionmentioning
confidence: 99%